What is it about intrauterine devices that women find unacceptable? Factors that make women non-users: a qualitative study. Issue 2 (1st April 2006) - Asker, Claire; Stokes-Lampard, Helen; Wilson, Sue; Beavan, Jackie
Abstract : Introduction: There is a lack of published research into the perceptions of 'non-users' of copper intrauterine contraceptive devices (IUDs). Despite this being one of the most commonly used methods of contraception in other countries, only 5% of contraceptive users in Great Britain aged 16–49 years currently use an IUD. This study explores how women's lay beliefs and perceptions about IUDs lead to rejection of this contraceptive choice. Methods: One-to-one semi-structured interviews were conducted with 10 women of varying ages and parity recruited from an urban general practice. None of the women had ever used IUDs but all had used contraception in the previous 6 months. Data were subjected to qualitative analysis. Results: Five analytical themes were identified: lack of objective information about IUDs, reported side effects of IUDs, anxieties about the process of fitting an IUD, IUDs as an infection risk and lack of personal control of an IUD, once fitted. Conclusions: Some of the themes identified mirrored those found in studies of user attitudes to and experiences of IUDs. Others, particularly the prominent worries about mess and embarrassment during fitting and the association between the hidden nature of the fitted device and unreliability, are new and need wider exploration.